COMMUNICATION STRATEGIES USED BY INFORMATION CENTER STAFF AT SACRED MONKEY FOREST UBUD - Adnyana, I W. A.; Wedhanti, N. K.; Agustini, D. A. E. (Universitas Pendidikan Ganesha, 2018)
The aim of this study was to analyze the types of communication strategies used by the Information Center Staff at Sacred Monkey Forest Ubud, the type of communication strategies mostly used by the staff, and the function of communication strategies used by the staff. In this study, the subject was the Information Center staff at Sacred Monkey Forest Ubud. Qualitative design was employed in this study. There were two methods of data collection were used namely; observation and interview. The findings of study show that there are eight types of communication strategies used by the staff, namely: message abandonment (6%), approximation (2%), non-linguistic signal (18%), literal translation (10%), foreign zing (6%), appeal for help (3%), stalling or time gaining (44%), and clarification request (11%). Time gaining is the type of communication strategies mostly used by the staff. There are two main functions of communication strategies used, namely; (1) to ovoid language difficulties and make the visitors easier to understand and is not confuse about the utterance, and (2) to make the communication more efficient and provide time to think. Keywords: communication strategies, information center, sacred monkey forest ubud